Hubungan Hasil Belajar Mata Pelajaran Projek Kreatif Dan Kewirausahaan Dengan Minat Berwirausaha Pada Peserta Didik Program Keahlian Kuliner SMKN 1 Cepu (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to describe: 1) Student learning outcomes regarding Creative Projects and Entrepreneurship (PKK) subjects; 2) Entrepreneurial interest of students at SMKN 1 Cepu; and 3) The relationship between PKK subject learning outcomes and students' interest in entrepreneurship. The method used in this research is a quantitative method and uses the Correlation Coefficient (r) test with a quantitative descriptive approach. In this study the sample was class XI students at SMKN 1 Cepu. The data collection technique uses a questionnaire method to measure interest in entrepreneurship and a documentation method for the final results of PKK subjects. The research results stated that: 1) the Creative Projects and Entrepreneurship subjects showed good results, with consistent and high scores; 2) students have a good interest in entrepreneurship, with consistent and high grades; and 3) the hypothesis results state that learning outcomes are not related to students' interest in entrepreneurship.